Sequencing nucleic acids: from chemistry to medicine - Balasubramanian, Shankar (2011)
Chemistry has played a vital role in making routine, affordable sequencing of human genomes a reality. This article focuses on the genesis and development of Solexa sequencing that originated in Cambridge, UK. This sequencing approach is helping transform science and offers intriguing prospects for the future of medicine.